COMPARATIVE ANALYSIS OF ARTEMETHER WITH LUMEFANTRINE TABLETS: A STUDY OF THREE PHARMACEUTICAL BRANDS (International Journal of Food and Nutritional Sciences, 2022)
This study aims to assess the physicochemical equivalence of eight brands of Artemether with Lumefantrine Tablets, an antimalarial drug combination, sourced from various retail pharmacy outlets in international markets. Method: Eight different brands of Artemether with Lumefantrine Tablets were evaluated for quality and physicochemical equivalence. The assessment included tests for uniformity of weight, friability, thickness, crushing strength, disintegration, and chemical assay of the tablets. Results: All brands of tablets met the standards set by the Indian Pharmacopoeia (IP) for uniformity of weight, disintegration, and crushing strength. Three brands also passed the friability test. The amounts of Artemether with Lumefantrine released from the different brands showed no significant difference (P > 0.05). Conclusion: Out of the eight brands analysed, only three (not registered by NAFDAC) met all the British Pharmacopoeia (BP) quality specifications and demonstrated physical and chemical equivalence. This study underscores the importance of continuous market surveillance to verify the equivalence of new products with the innovator product.